(untitled) (Altre Modernità, 2015)
The image of the window in Vasyl Stus’s poetry has not been satisfactorily investigated. A major Ukrainian poet of the twentieth century, Stus shows in his oeuvre a very interesting application of this topos, marked by a striking semantic variety. Though not numerous, his windows cover a wide range of meanings. They can be linked to divine grace, imprisonment, as well as poetic inspiration. This article inquires into the evolution of Stus’s lyrical representations of the window from his early poetry up to his masterpieces Čas tvorčosti and Palimpsesty, speculating on possible intertextual links with authors such as Boris Pasternak and Marina Cvetaeva.